2009
DOI: 10.4197/sci.21-2.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Neem Products on the Mortality and Fitness of Adult Schistocerca gregaria (Forskal)

Abstract: Abstract. Various neem products were tested against resting and flying Schistocerca gregaria. Two of the products namely neem Azal-F and the unclarified neem oil were obtained from the Company Trifolio, whereas neem oil enriched and pure neem oil, were a gift of Prof. Schmutterer (University of Giessen). The treatment during flight activity caused, for all products applied an increase of the mortality rate, except the neem oil enriched and pure neem oil of Giessen, up to 70 and 90% respectively. The same produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…dose diluted in vegetable oil. Al-Fifi (2009) tested various Neem products against resting and flying S. gregaria the treatment during flight activity caused, for all products applied an increase of the mortality rate, except the Neem oil enriched and pure Neem oil of Giessen, up to 70 and 90% respectively. Ghazawy, et al (2010) concluded that after suitable field trials, the use of azadirachtin may be a viable alternative to chemical insecticides for control of grasshoppers in Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…dose diluted in vegetable oil. Al-Fifi (2009) tested various Neem products against resting and flying S. gregaria the treatment during flight activity caused, for all products applied an increase of the mortality rate, except the Neem oil enriched and pure Neem oil of Giessen, up to 70 and 90% respectively. Ghazawy, et al (2010) concluded that after suitable field trials, the use of azadirachtin may be a viable alternative to chemical insecticides for control of grasshoppers in Egypt.…”
Section: Resultsmentioning
confidence: 99%